Preparation, Characterization, and In Vivo Evaluation of an Oral Multiple Nanoemulsive System for Co-Delivery of Pemetrexed and Quercetin - Rudra Pangeni; Vijay Kumar Panthi; In-Soo Yoon; Jin Woo Park (MDPI AG, 2018)
Co-administration of conventional and natural chemotherapeutics offers synergistic anticancer efficacy while minimizing adverse effects. In this study, an oral co-delivery system for pemetrexed (PMX) and quercetin (QCN) was designed based on water-in-oil-in-water nanoemulsion (NE), which is highly absorbable because it enhances the intestinal membrane permeability of PMX and aqueous solubility of QCN. To create this system, an ion-pairing complex of PMX with Nα-deoxycholyl-l-lysyl-methylester (DCK) was formed and further incorporated with QCN into the NE, yielding PMX/DCK-QCN-NE. The results revealed synergistic inhibitory effects on human lung carcinoma (A549) cell proliferation and migration after combined treatment with PMX/DCK and QCN. The intestinal membrane permeability and cellular uptake of PMX/DCK and QCN from the NE were significantly improved via facilitated transport of PMX by the interaction of DCK with bile acid transporters, as well as NE formulation-mediated alterations in the membrane structure and fluidity, which resulted in 4.51- and 23.9-fold greater oral bioavailability of PMX and QCN, respectively, than each free drug. Tumor growth in A549 cell-bearing mice was also maximally suppressed by 62.7% after daily oral administration of PMX/DCK-QCN-NE compared with controls. Thus, PMX/DCK-QCN-NE is a promising oral nanocarrier of PMX and QCN for synergistic anticancer efficacy and long-term chemotherapy.